Prevalence of the consumption of anticholinergic drugs in HIV patients - Ricardo Zafra-Morales; Yared González-Pérez; María José Nebot-Villacampa; Jara Gallardo-Anciano; Raquel Marín-Gorricho; Andrea Casajús-Navasal (Elsevier, 2018)
Objective: To analyse anticholinergic agent consumption in HIV patients 50 years or older; to determine anticholinergic risk using the ACB and ARS scales; and to determine if these patients use any type of benzodiazepine. Method: A descriptive observational study of 256 HIV patients 50 years or older. Results: 73.1% were men. Mean age was 56 ± 5.9 years. 55.9% of the patients were coinfected with HCV. Excluding HIV drugs, mean drug consumption was 2.9 ± 2.9 drugs per patient. The ACB and ARS scales showed that 26.2% and 17.2% of the patients took an anticholinergic agent, and that 43.3% and 36.4% presented high anticholinergic risk, respectively. 30.5% of patients consumed benzodiazepines. Conclusions: The percentage of HIV patients aged 50 years or older who were taking anticholinergic agents was statistically significantly higher on the ACB scale than on the ARS scale. No studies are available on the HIV population with which to compare our results, but there is evidence that this group of drugs can affect older adults.